非アルコール性脂肪性肝炎（ＮＡＳＨ）または肝細胞癌（ＨＣＣ）を診断するためのバイオマーカー (2023)
本明細書に記載の実施形態は、概して、疾患進行過程を進んでいる疾患状態の診断及び／または治療のためにペプチド構造を分析するための技術に関する。本願に記載される技術に関連する方法の非限定的な例は、対象から得られる生体試料に対応するペプチド構造データを受信することと、ペプチド構造プロファイルを特定することと、疾患進行過程内の疾患状態を診断することと、を含んでもよい。本例は、疾患状態に関連する診断出力を生成することを更に含んでもよい。少なくともある場合には、ペプチド構造プロファイルは、グリコシル化ペプチド、脱グリコシル化ペプチド、またはその両方を含んでもよい。【選択図】図３ Embodiments described herein generally relate to technologies for analyzing peptide structures for diagnosing and/or treating a disease state advancing through a disease progression. A non-limiting example of a method relating to the technologies described in the subject application may include receiving peptide structure data corresponding to the biological sample obtained from the subject, identifying a peptide structure profile, and diagnosing a disease state within a disease progression. The example may further include generating a diagnosis output relating to the disease state. In at least some cases, the peptide structure profile may include glycosylated peptides, aglycosylated peptides, or both.